A novel approach to treating post-stroke depression: administration of Botulinum Toxin A via local facial injection - Feng, Xiao-Yan; Shen, Ting-Ting; Wu, Qian-Chang; Wang, Jun; Ni, Ping; Liu, Jing; Zhou, Xu-Ping; Hu, Hua; Luo, Wei-Feng (Frontiers in Neurology, 2024)
Background: Post-stroke depression (PSD) is a frequent complication following a stroke, characterized by prolonged feelings of sadness and loss of interest, which can significantly impede stroke rehabilitation, increase disability, and raise mortality rates. Traditional antidepressants often have significant side effects and poor patient adherence, necessitating the exploration of more suitable treatments for PSD. Previous researchers and our research team have discovered that Botulinum Toxin A (BoNT-A) exhibits antidepressant effects. Therefore, our objective was to assess the efficacy and side effects of BoNT-A treatment in patients with PSD. Methods: A total of 71 stroke patients meeting the inclusion criteria were allocated to the two group. 2 cases were excluded due to severe neurological dysfunction that prevented cooperation and 4 cases were lost follow-up. Ultimately, number of participants in the BoNT-A group (n=32) and sertraline group (n=33). Treatment efficacy was evaluated 1, 2, 4, 8 and 12 weeks post-treatment. Results: There were no significant differences in baseline characteristics between the two groups (P>0.05). Both groups exhibited comparable treatment efficacy, with fewer side effects observed in the BoNT-A group compared to the Sertraline group. BoNT-A therapy demonstrated significant effects as early as the first week (P<0.05), and by the 12th week, there was a notable decrease in neuropsychological scores, significantly lower than the baseline level. The analysis revealed significant differences in measurements of the Hamilton Depression Scale (HAMD) (F(770)=12.547, P=0.000), Hamilton Anxiety Scale (HAMA) (F(951)=10.422, P=0.000), Self-Rating Depression Scale (SDS) (F(1385)=10.607, P=0.000), and Self-Rating Anxiety Scale (SAS) (F(1482)=11.491, P=0.000). Conclusion: BoNT-A treatment effectively reduces depression symptoms in patients with PSD on a continuous basis.